Blurred Aerial Photography of Serials (KULT_online, 2010)
The anthology Was bisher geschah (Previously On…) succeeds in representing the variety of contemporary American TV serials. Considering the limited length, there are surprisingly concise and gainful analyses to be found here; some articles, however, suffer from an inconsistent master plan and over-simplifications. These simplifications result in the contrary of the publishers' desire to show the quality and complexity of the serials.